Development and validation of RP-HPLC method for the determination of Darifenacin Hydrobromide in bulk drug and pharmaceutical dosage form - Acharya, Ankit; Satish, N.K.; Manoj, L.; Chitti, Renukaradhya (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The main objective of present study is to develop and validate a new, simple, precise and accurate RP-HPLC method for the determination of Darifenacin Hydrobromide (DFH) in bulk and pharmaceutical dosage forms. The separation and quantification of the drug was achieved on a RP C18 column (250×4.6mm, 5μm) using a mobile phase of acetonitrile: buffer (50:50), pH 3.0 ± 0.2 at a flow rate of 1 mL/min with detection of analyte at 287 nm. The separation was achieved with in 4.0 ± 0.3 min. The method showed good linearity in the range of 10-100 μg/mL. The intra and inter day RSD ranged from 0.20-0.58%. The recovery (mean ± SD) of low, medium and high concentrations were 98.50 ± 0.20, 100.27 ± 0.15 and 100.90 ± 0.09 respectively. The limit of detection and limit of quantification were 0.31 and 0.61 μg/mL, respectively. It can be concluded that the present method could be superior over the methods which were reported earlier. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 1, 2017, Page: 36-44